The Full Globin Repertoire of Turtles Provides Insights into Vertebrate Globin Evolution and Functions - Schwarze, Kim (Genome Biol Evol, 2015)
Globins are small heme proteins that play an important role in oxygen supply, but may also have other functions. Globins offer a unique opportunity to study the functional evolution of genes and proteins. We have characterized the globin repertoire of two different turtle species: the Chinese softshell turtle (Pelodiscus sinensis) and the western painted turtle (Chrysemys picta bellii). In the genomes of both species, we have identified eight distinct globin types: hemoglobin (Hb), myoglobin, neuroglobin, cytoglobin, globin E, globin X, globin Y, and androglobin. Therefore, along with the coelacanth, turtles are so far the only known vertebrates with a full globin repertoire. This fact allows for the first time a comparative analysis of the expression of all eight globins in a single species. Phylogenetic analysis showed an early divergence of neuroglobin and globin X before the radiation of vertebrates. Among the other globins, cytoglobin diverged first, and there is a close relationship between myoglobin and globin E; the position of globin Y is not resolved. The globin E gene was selectively lost in the green anole, and the genes coding for globin X and globin Y were deleted in chicken. Quantitative real-time reverse transcription polymerase chain reaction experiments revealed that myoglobin, neuroglobin, and globin E are highly expressed with tissue-specific patterns, which are in line with their roles in the oxidative metabolism of the striated muscles, the brain, and the retina, respectively. Histochemical analyses showed high levels of globin E in the pigment epithelium of the eye. Globin E probably has a myoglobin-like role in transporting O(2) across the pigment epithelium to supply in the metabolically highly active retina.